Aplikasi Rantai Markov pada Perpindahan Konsumen Merek Sabun Mandi - Santoso, Louis Vigo; Rajagukguk, Rikardo Jordan; Wilantara, I Gede Ligar Nouvaldi; Putera, Judha Dana; Nurahmadiningsi, Nurahmadiningsi; Dwi Octavanny, Made Ayu (Jurnal Matematika; Vol 13 No 1 (2023)DO - 10.24843/JMAT.2023.v13.i01.p160, 2023)
The purpose of this study is to determine the market share for several future periods of the Lifebuoy, NUVO, Dettol, and other soap brands and the market share when equilibrium conditions are reached by applying the markov chain to the movement of soap consumers. Markov chain is a method for analyzing the properties of a variable in the present based on past properties to interpret the properties of these variables in the future. The results showed that the highest market share was held by Lifebuoy with 37.6% and followed by other brands (25.7%), Dettol (20.2%), and NUVO (16.5%). In subsequent periods the market share of Lifebuoy, NUVO and Dettol has increased while the other brands have decreased. The market share when the equilibrium condition is reached is Lifebuoy (37.8%), other brands (24.2%), Dettol (21.1%), and NUVO (16.9%).